Microbiological study of urinary tract infection in patient visiting paropkar maternity and women's hospital Thapathali, Kathmandu. - Subedi, Bandana (2010)
ABSTRACT: This study was conducted in patients visiting Paropakar Maternity and Women's Hospital, Thapathali, with an objective to assess the Microbiological study of Urinary Tract Infection. Annually, women and their neonates are in the risk of morbidity and mortality due to UTI in case of Nepal. In this study, a total of 1246 clinical samples of urine were collected. Prevalence of uropathogens was found 29.61% (369/1246). A total of 369 uropathogens of which 8 species from Gram negative (82.66%) and 4 species from Gram positive (17.34%) were isolated. In Gram negative, the most predominant was E. coli (62.3%) followed by Klebsiella pneumoniae (6.5%), Proteus mirabilis (4.9%), K. oxytoca (3%), P. vulgaris (2.7%), Enterobacter cloacae (0.5%) and Citrobacter freundii (0.5%). From Gram positive most prevalent were Staphylococcus aureus (7.6%) and coagulase negative staphylococci (CoNS) (7.6%) followed by Streptococcus spp. (1.4%) and S. fecalis (0.8%). The most efficient antibiotics in Gram negatives were found Tobramycin (87.54%). In S. aureus Amikacin (96.43%) was found more susceptible whereas for CoNS and Streptococcus spp. maximal efficient antibiotic was found Nitrofurantoin (75%). Altogether 199 Multidrug resistant strains were isolated. Highest percent of MDR were found in K. pneumoniae (58.33%) in Gram negatives and S. aureus (82.14%) in Gram positives urine isolates, a total of 14 Methicillin Resistant Staphylococcus aureus (MRSA) were isolated. All MRSA isolates were found to be Vancomycin sensitive. Mutiple Antibiotics Resistance index (MARI) of isolates was found more than 0.20 in 247 (66.93%) of isolates. MARI of antibiotics was found highest in antibiotics Nalidixic acid in Gram negative and Moxifloxacin in S. aureus and Penicillin G in CoNS and Streptococcus spp. Previous antibiotics use was found significantly associated with MDR isolates (p=0.029; OR=1.752 CI=1.159 and 2.650). Keywords: Host factors, MARI, uropathogens